Preparation process for compact silicon carbide coating on surface of carbon fiber thermal insulation material
By forming a graphite sealing blocking layer and a double-layer silicon carbide coating on the carbon fiber insulation material, the problem of insufficient sealing properties of carbon fiber insulation materials and low coating bonding strength in high temperature environments is solved, and the thermal insulation performance and crack resistance are improved , and reduces production costs.
Patent Information
- Application Number
- CN202411352232.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing carbon fiber insulation materials have problems such as insufficient sealing properties and low coating bonding strength in high temperature environments, resulting in poor thermal insulation performance and high production costs.
After polishing and polishing the surface of the hard carbon fiber felt matrix, the zirconium nitrate solution is coated and carbonized at high temperature to form a graphite sealed blocking layer, and then a double-layer silicon carbide coating is formed on it, including a crack-resistant layer and a dense layer, through silicon carbide The coordination between nanowires and gas-phase silicon source improves the density and bonding strength of the coating.
It significantly improves the sealing property of carbon fiber insulation materials and the bonding strength between the coating and the substrate, enhances crack resistance and denseness, reduces production costs, and is suitable for high-temperature environments.
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation materials, in particular to a process for preparing a dense silicon carbide coating on the surface of a carbon fiber thermal insulation material. Background Art
[0002] Hard carbon fiber felt has the characteristics of low density, high stability, ablation resistance, corrosion resistance and excellent high-temperature mechanical properties. At the same time, there are a large number of micropores inside, which makes it have outstanding high-temperature thermal insulation performance. Therefore, it is a material that can be used in high-temperature environments. Silicon carbide, as an excellent high-temperature structural ceramic, is considered to be a high-temperature wear-resistant structural material with broad application prospects. Since silicon carbide has a small thermal expansion coefficient and has good physical and chemical compatibility and similar thermal expansion coefficients with carbon materials, it is used as one of the best coating materials for high-temperature wear resistance and corrosion resistance. The oxidation resistance, scouring resistance and erosion resistance of silicon carbide coatings are better than other carbon-based coatings and coatings. The present invention provides a process for preparing a dense silicon carbide coating on the surface of a carbon fiber thermal insulation material. The silicon carbide coating prepared by the present invention has a high bonding strength between the coating and the substrate, and also has the advantages of simple process and low production cost. Summary of the invention
[0003] The present invention provides a process for preparing a dense silicon carbide coating on the surface of a carbon fiber thermal insulation material, comprising: performing surface treatment on a hard carbon fiber felt substrate, uniformly coating the treated substrate surface with graphite emulsion, and forming a graphite sealing blocking layer on the substrate surface after carbonization and graphitization treatment; generating a double-layer silicon carbide coating on the surface of the graphite sealing blocking layer, comprising an anti-cracking layer and a dense layer. The product prepared by the present invention improves the strength of the coating covering the substrate surface, and the silicon carbide coating prepared on this basis effectively improves the bonding strength between the coating and the substrate, and also has the advantages of simple process, low production cost, etc.
[0004] A preparation process for a dense silicon carbide coating on the surface of a carbon fiber thermal insulation material, characterized in that the process comprises:
[0005] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution, and drying it;
[0006] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of a carbon source gas and an inert gas, carbonizing at high temperature, and cooling to room temperature;
[0007] 3) dispersing graphite emulsion, polycarbosilane and nano silicon powder in tetrachloroethylene, adding vinyl triethoxysilane, coating the obtained slurry on the surface of the product in step 2, drying and placing in a high temperature furnace, heating and carbonizing under a closed or inert atmosphere, and then heating and graphitizing to obtain a graphite layer;
[0008] 4) mixing the silicon carbide nanowires and the silane coupling agent, adding them to toluene, heating and activating them, and then drying them; dispersing the dried silicon carbide nanowires in an aqueous solution containing a carbon source precursor, stirring them evenly, filtering them, drying them, and then placing them in a high-temperature furnace for high-temperature carbonization under inert gas protection to obtain modified silicon carbide nanowires;
[0009] 5) Dispersing the modified silicon carbide nanowires, polycarbosilane, and silicon powder in tetrachloroethylene, adding vinyltriethoxysilane, coating the obtained slurry on the surface of the product in step 3, placing it in a high-temperature furnace, and heating it in a sealed or inert atmosphere to react and generate a silicon carbide layer;
[0010] 6) Phenolic resin, fumed silica powder and ethylene glycol are uniformly mixed to obtain slurry; the slurry is coated on the surface of the product in step 5, placed in a high-temperature furnace, a mixed gas of monosilane and hydrogen is introduced, and heated to obtain a carbon fiber thermal insulation material.
[0011] Furthermore, in step 1, the concentration of the zirconium nitrate solution is 1-5wt%.
[0012] Furthermore, in step 2, a mixed gas of a carbon source gas and an inert gas in a volume ratio of 1:2-3 is introduced, and the temperature is raised to 900-1000° C. and maintained for 2-4 hours.
[0013] Furthermore, in the step 3, graphite emulsion, polycarbosilane with a molecular weight of 1000-2000, and silicon powder with a size of 100-150 nm are dispersed in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder and tetrachloroethylene is 100:25-50:20-30:150-200, and then vinyl triethoxysilane is added, wherein the mass ratio of vinyl triethoxysilane to the slurry is 2-5:100; the slurry is coated on the surface of the product in step 2, dried and placed in a high-temperature furnace, and heated to 1100-1300° C. in a sealed or inert atmosphere, maintained for 0.5-2 h, and then heated to 1800-2000° C. for graphitization, maintained for 0.5-1 h.
[0014] Furthermore, in the step 4, the silicon carbide nanowires and aminopropyltriethoxysilane are mixed in a mass ratio of 10:1-2, then added to toluene, heated for 4-6 hours for activation, and then dried; the dried silicon carbide nanowires are dispersed in an aqueous solution containing a carbon source precursor with a concentration of 15-20wt%, stirred evenly, filtered, dried, and then placed in a high-temperature furnace, heated to 600-700°C under inert gas protection for high-temperature carbonization to obtain modified silicon carbide nanowires.
[0015] Furthermore, in the step 5, the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1000-2000, and silicon powder with a particle size of 100-150 nm are dispersed in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 15-20:25-50:20-30:150-200, and then vinyl triethoxysilane is added, wherein the mass ratio of vinyl triethoxysilane to the slurry is 2-5:100; the slurry is coated on the surface of the product in step 3, placed in a high-temperature furnace, and heated at 1600-1800° C. in a closed or inert atmosphere for 1-4 hours.
[0016] Furthermore, in the step 6, phenolic resin, fumed silica powder, and ethylene glycol are uniformly mixed in a mass ratio of 50-60:50-60:140-160 to obtain a slurry; the slurry is coated on the surface of the product in step 5, placed in a high-temperature furnace, and a mixed gas of monosilane and hydrogen in a volume ratio of 1:2-4 is introduced, the temperature is raised to 850-950°C, maintained for 10-16h, and cooled to obtain a carbon fiber thermal insulation material.
[0017] A carbon fiber thermal insulation material is obtained by adopting the preparation process.
[0018] Advantageous technical effects of the present invention compared to the prior art
[0019] 1) Sealing carbon fiber felt substrate: carbon deposition modification is performed on the surface of the hard carbon fiber felt substrate, zirconium nitrate is converted into zirconium oxide at high temperature, a carbon layer with high roughness is formed on the substrate surface under the catalytic action of zirconium oxide, graphite emulsion is coated on the surface of the carbon layer, and the volatilization of tetrachloroethylene at high temperature can remove metal impurities in the graphite, thereby forming a graphite sealing blocking layer with a dense structure that is tightly combined with the substrate after high temperature treatment;
[0020] 2) Improve the bonding strength of the silicon carbide coating: The graphite sealing blocking layer has a certain adhesion, which can further improve the strength of the silicon carbide coating covering the substrate surface coating, and can prevent silicon from diffusing into the substrate during high-temperature sintering, thereby forming a dense silicon carbide coating on the surface of the blocking layer.
[0021] 3) Improving the crack resistance and density of silicon carbide: The silicon carbide coating includes a two-layer structure. The silicon carbide coating at the bottom layer is added with silicon carbide nanowires. The silicon carbide nanowires in the layer can improve the fracture resistance of the coating, thereby increasing the toughness of the coating. At the same time, a high-temperature resistant protective layer is formed on the surface of the silicon carbide nanowires, and the silicon carbide nanowires are destroyed during high-temperature sintering. The silicon carbide nanowires are coated with a carbon coating to improve the bonding strength between the silicon carbide nanowires and the silicon carbide coating, thereby ensuring the mechanical properties of the coating. During the sintering process, a gas-phase silicon source is added to the silicon carbide coating at the surface for deposition, and silicon carbide is generated by in-situ reaction on the surface of the coating and in the pores, thereby improving the density of the coating surface.
[0022] 4) The preparation process of the present invention has low cost, simple process, simple and efficient, and has the value of wide application. DETAILED DESCRIPTION
[0023] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0024] Example 1
[0025] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 3wt%, and drying it;
[0026] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2, heating to 900° C., maintaining for 4 hours; and cooling to room temperature;
[0027] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 100 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:25:20:150, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 2:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2 , after drying, place in a high temperature furnace, heat to 1100°C under nitrogen protection, keep for 2h, then heat to 1800°C, keep for 1h;
[0028] 4) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:1 and dispersed in toluene, heated at 75°C for 4 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 15wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 600°C under nitrogen protection, and maintained for 8 hours to obtain modified silicon carbide nanowires;
[0029] 5) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 100 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 15:25:20:150, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 2:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1600℃ in a sealed or inert atmosphere, and maintained for 4h;
[0030] 6) Phenolic resin, fumed silica powder and ethylene glycol are mixed in a mass ratio of 50:50:140 to obtain a slurry; the slurry is applied on the surface of the product in step 5, and the amount of the coating slurry is 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen in a volume ratio of 1:2, heated to 850°C, maintained for 16 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0031] Example 2
[0032] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 5wt%, and drying it;
[0033] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:3, heating to 1000° C., maintaining for 2 h; and cooling to room temperature;
[0034] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 100 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:50:30:200, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 5:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2, after drying, place in a high temperature furnace, heat to 1300°C under nitrogen protection, keep for 0.5h, then heat to 2000°C, keep for 0.5h;
[0035] 4) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:2 and dispersed in toluene, heated at 75°C for 6 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 20wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 700°C under nitrogen protection, and maintained for 4 hours to obtain modified silicon carbide nanowires;
[0036] 5) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 150 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 20:50:30:200, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 5:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1800℃ in a sealed or inert atmosphere, and maintained for 1h;
[0037] 6) Phenolic resin, fumed silica powder and ethylene glycol are mixed in a mass ratio of 60:60:160 to obtain a slurry; the slurry is applied on the surface of the product in step 5, and the amount of the coating slurry is 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen with a volume ratio of 1:4, heated to 950°C, maintained for 10 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0038] Example 3
[0039] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 3wt%, and drying it;
[0040] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2.5, heating to 950° C., maintaining for 3 hours; and cooling to room temperature;
[0041] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2 , after drying, place in a high temperature furnace, heat to 1200℃ under nitrogen protection, keep for 1h, then heat to 1900℃, keep for 1h;
[0042] 4) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:2 and dispersed in toluene, heated at 75°C for 5 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 18wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 650°C under nitrogen protection, and maintained for 6 hours to obtain modified silicon carbide nanowires;
[0043] 5) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 120 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 18:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1700℃ in a sealed or inert atmosphere, and maintained for 2h;
[0044] 6) Phenolic resin, fumed silica powder and ethylene glycol were mixed in a mass ratio of 55:55:150 to obtain a slurry; the slurry was applied on the surface of the product in step 5, and the amount of the coating slurry was 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen with a volume ratio of 1:3, heated to 900°C, maintained for 12 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0045] Comparative Example 1 (no carbon deposition)
[0046] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, and drying it;
[0047] 2) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 1, and the amount of the coating slurry is 0.5 kg / m 2 , after drying, place in a high temperature furnace, heat to 1200℃ under nitrogen protection, keep for 1h, then heat to 1900℃, keep for 1h;
[0048] 3) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:2 and dispersed in toluene, heated at 75°C for 5 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 18wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 650°C under nitrogen protection, and maintained for 6 hours to obtain modified silicon carbide nanowires;
[0049] 4) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 120 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 18:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1700℃ in a sealed or inert atmosphere, and maintained for 2h;
[0050] 5) Phenolic resin, fumed silica powder and ethylene glycol were mixed in a mass ratio of 55:55:150 to obtain a slurry; the slurry was applied on the surface of the product in step 4, and the amount of the coating slurry was 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen with a volume ratio of 1:3, heated to 900°C, maintained for 12 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0051] Comparative Example 2 (no graphite layer applied)
[0052] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 3wt%, and drying it;
[0053] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2.5, heating to 950° C., maintaining for 3 hours; and cooling to room temperature;
[0054] 3) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:2 and dispersed in toluene, heated at 75°C for 5 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 18wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 650°C under nitrogen protection, and maintained for 6 hours to obtain modified silicon carbide nanowires;
[0055] 4) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 120 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 18:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1700℃ in a sealed or inert atmosphere, and maintained for 2h;
[0056] 5) Phenolic resin, fumed silica powder and ethylene glycol were mixed in a mass ratio of 55:55:150 to obtain a slurry; the slurry was applied on the surface of the product in step 4, and the amount of the coating slurry was 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen with a volume ratio of 1:3, heated to 900°C, maintained for 12 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0057] Comparative Example 3 (without adding silicon carbide nanowires)
[0058] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 3wt%, and drying it;
[0059] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2.5, heating to 950° C., maintaining for 3 hours; and cooling to room temperature;
[0060] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2 , after drying, place in a high temperature furnace, heat to 1200℃ under nitrogen protection, keep for 1h, then heat to 1900℃, keep for 1h;
[0061] 4) Dispersing polycarbosilane with a molecular weight of 1500 and silicon powder with a size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of polycarbosilane, silicon powder and tetrachloroethylene is 35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1700℃ in a sealed or inert atmosphere, and maintained for 2h;
[0062] 5) Phenolic resin, fumed silica powder and ethylene glycol were mixed in a mass ratio of 55:55:150 to obtain a slurry; the slurry was applied on the surface of the product in step 4, and the amount of the coating slurry was 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen with a volume ratio of 1:3, heated to 900°C, maintained for 12 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0063] Comparative Example 4 (no surface dense layer applied)
[0064] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 3wt%, and drying it;
[0065] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2.5, heating to 950° C., maintaining for 3 hours; and cooling to room temperature;
[0066] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2, after drying, place in a high temperature furnace, heat to 1200℃ under nitrogen protection, keep for 1h, then heat to 1900℃, keep for 1h;
[0067] 4) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:2 and dispersed in toluene, heated at 75°C for 5 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 18wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 650°C under nitrogen protection, and maintained for 6 hours to obtain modified silicon carbide nanowires;
[0068] 5) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 120 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 18:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high-temperature furnace, heated to 1700°C in a closed or inert atmosphere, and maintained for 2 hours; a carbon fiber thermal insulation material is obtained.
[0069] Comparative Example 5 (substrate not modified with zirconium nitrate)
[0070] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, and drying it;
[0071] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2.5, heating to 950° C., maintaining for 3 hours; and cooling to room temperature;
[0072] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2 , after drying, place in a high temperature furnace, heat to 1200℃ under nitrogen protection, keep for 1h, then heat to 1900℃, keep for 1h;
[0073] 4) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:2 and dispersed in toluene, heated at 75°C for 5 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 18wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 650°C under nitrogen protection, and maintained for 6 hours to obtain modified silicon carbide nanowires;
[0074] 5) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 120 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 18:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1700℃ in a sealed or inert atmosphere, and maintained for 2h;
[0075] 6) Phenolic resin, fumed silica powder and ethylene glycol were mixed in a mass ratio of 55:55:150 to obtain a slurry; the slurry was applied on the surface of the product in step 5, and the amount of the coating slurry was 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen with a volume ratio of 1:3, heated to 900°C, maintained for 12 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0076] Comparative Example 6 (Silane gas deposition was not added to the surface layer)
[0077] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 3wt%, and drying it;
[0078] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2.5, heating to 950° C., maintaining for 3 hours; and cooling to room temperature;
[0079] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2, after drying, place in a high temperature furnace, heat to 1200℃ under nitrogen protection, keep for 1h, then heat to 1900℃, keep for 1h;
[0080] 4) Silicon carbide nanowires with a diameter of 0.5 micrometers and a length of 1 mm and aminopropyltriethoxysilane were mixed in a mass ratio of 10:2 and dispersed in toluene, heated at 75°C for 5 hours for activation, and then dried; the dried silicon carbide nanowires were dispersed in a glucose aqueous solution containing a concentration of 18wt%, and the mass ratio of the silicon carbide nanowires to the glucose aqueous solution was 1:10. After stirring evenly, the mixture was filtered and dried, and then placed in a high-temperature furnace, heated to 650°C under nitrogen protection, and maintained for 6 hours to obtain modified silicon carbide nanowires;
[0081] 5) Dispersing the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1500, and 120 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 18:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1700℃ in a sealed or inert atmosphere, and maintained for 2h;
[0082] 6) Phenolic resin, fumed silica powder and ethylene glycol were mixed in a mass ratio of 55:55:150 to obtain a slurry; the slurry was applied on the surface of the product in step 5, and the amount of the coating slurry was 0.3 kg / m 2 , placed in a high temperature furnace, heated to 900°C, maintained for 12 hours, cooled, and obtained a carbon fiber thermal insulation material.
[0083] Comparative Example 7 (unmodified silicon carbide nanowires)
[0084] 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution with a concentration of 3wt%, and drying it;
[0085] 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of acetylene and nitrogen in a volume ratio of 1:2.5, heating to 950° C., maintaining for 3 hours; and cooling to room temperature;
[0086] 3) dispersing graphite emulsion, polycarbosilane with a molecular weight of 1500, and silicon powder with a particle size of 120 nm in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder, and tetrachloroethylene is 100:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 2, and the amount of the coating slurry is 0.5 kg / m 2 , after drying, place in a high temperature furnace, heat to 1200℃ under nitrogen protection, keep for 1h, then heat to 1900℃, keep for 1h;
[0087] 4) dispersing silicon carbide nanowires with a diameter of 0.5 microns and a length of 1 mm, polycarbosilane with a molecular weight of 1500, and 120 nm silicon powder in tetrachloroethylene to obtain a slurry, wherein the mass ratio of silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 18:35:25:180, and then adding vinyl triethoxysilane, wherein the mass ratio of vinyl triethoxysilane to the slurry is 4:100; coating the slurry on the surface of the product in step 3, and the amount of the coating slurry is 1.0 kg / m 2 , placed in a high temperature furnace, heated to 1700℃ in a sealed or inert atmosphere, and maintained for 2h;
[0088] 5) Phenolic resin, fumed silica powder and ethylene glycol were mixed in a mass ratio of 55:55:150 to obtain a slurry; the slurry was applied on the surface of the product in step 4, and the amount of the coating slurry was 0.3 kg / m 2 , placed in a high-temperature furnace, introduced a mixed gas of monosilane and hydrogen with a volume ratio of 1:3, heated to 900°C, maintained for 12 hours, and cooled to obtain a carbon fiber thermal insulation material.
[0089] Test Data
[0090] The product performance in the examples and comparative examples of the present invention was tested, and the examples were formed by changing the parameters of the preparation process of the present invention, in order to demonstrate the influence of the process parameters of the present invention on the product performance.
[0091] The test sample is tested on a Vickers hardness tester to measure the Young's modulus of the sample; the Vickers hardness of the sample, the crack length, and the fracture toughness K are calculated based on the applied load IC , where the material strain hardening exponent, i.e., the indenter parameter, is set to 0.016;
[0092] After oxidation in air at 1200℃ for 72h, weigh the sample and calculate the weight loss rate;
[0093] The results are shown in Table 1.
[0094] Table 1
[0095] <![CDATA[Fracture toughness value K IC (MPa / m 0.5 )]]> Weight loss rate (%) Example 1 5.68 0.212 Example 2 5.85 0.205 Example 3 5.76 0.210 Comparative Example 1 4.25 0.295 Comparative Example 2 3.82 0.340 Comparative Example 3 3.05 0.285 Comparative Example 4 4.05 0.372 Comparative Example 5 5.05 0.280 Comparative Example 6 5.65 0.274 Comparative Example 7 5.15 0.230
[0096] By comparing the embodiments and the comparative examples, it can be seen that the preparation process of the graphite sealing isolation layer and the surface dense layer has a greater influence on the weight loss rate, while the addition of silicon carbide nanowires and the surface treatment have a greater influence on the fracture toughness value. In addition, by comparing the processes, it can be seen that the modification of zirconium salts and the selection of atmosphere in the preparation of the dense layer also have a significant impact on the performance.
[0097] Graphite emulsion is coated on the surface of the carbon layer, and the volatilization of tetrachloroethylene at high temperature can remove metal impurities in the graphite, thereby forming a graphite sealing blocking layer with a dense structure that is tightly combined with the substrate after high-temperature treatment; the graphite sealing blocking layer has a certain adhesion force, which can further improve the strength of the silicon carbide coating covering the surface of the substrate, and can prevent silicon from diffusing into the interior of the substrate during high-temperature sintering, thereby forming a dense silicon carbide coating on the surface of the blocking layer.
[0098] During the sintering process, a gas phase silicon source is added to the surface silicon carbide coating for deposition, and silicon carbide is generated by in-situ reaction on the coating surface and in the pores, thereby improving the density of the coating surface.
[0099] Improve the crack resistance and density of silicon carbide: The silicon carbide coating includes a two-layer structure. The silicon carbide coating at the bottom layer is added with silicon carbide nanowires. The silicon carbide nanowires in the layer can improve the coating's fracture resistance, thereby increasing the coating's toughness. At the same time, a high-temperature resistant protective layer is formed on the surface of the silicon carbide nanowires, and the silicon carbide nanowires are destroyed during high-temperature sintering. The silicon carbide nanowires are coated with a carbon coating to improve the bonding strength between the silicon carbide nanowires and the silicon carbide coating, thereby ensuring the mechanical properties of the coating.
[0100] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A process for preparing a dense silicon carbide coating on the surface of a carbon fiber thermal insulation material, characterized in that: The process comprises: 1) grinding and polishing the surface of the hard carbon fiber felt substrate, ultrasonically cleaning it in anhydrous ethanol, drying it, coating the surface of the substrate with a zirconium nitrate solution, and drying it; 2) placing the product of step 1 in a high temperature furnace, introducing a mixed gas of a carbon source gas and an inert gas, carbonizing at high temperature, and cooling to room temperature; 3) dispersing graphite emulsion, polycarbosilane and nano silicon powder in tetrachloroethylene, adding vinyl triethoxysilane, coating the obtained slurry on the surface of the product in step 2, drying and placing in a high temperature furnace, heating and carbonizing under a closed or inert atmosphere, and then heating and graphitizing to obtain a graphite layer; 4) mixing the silicon carbide nanowires and the silane coupling agent, adding them to toluene, heating and activating them, and then drying them; dispersing the dried silicon carbide nanowires in an aqueous solution containing a carbon source precursor, stirring them evenly, filtering them, drying them, and then placing them in a high-temperature furnace for high-temperature carbonization under inert gas protection to obtain modified silicon carbide nanowires; 5) Dispersing the modified silicon carbide nanowires, polycarbosilane, and silicon powder in tetrachloroethylene, adding vinyltriethoxysilane, coating the obtained slurry on the surface of the product in step 3, placing it in a high-temperature furnace, and heating it in a sealed or inert atmosphere to react and generate a silicon carbide layer; 6) Phenolic resin, fumed silica powder and ethylene glycol are uniformly mixed to obtain slurry; the slurry is coated on the surface of the product in step 5, placed in a high-temperature furnace, a mixed gas of monosilane and hydrogen is introduced, and heated to obtain a carbon fiber thermal insulation material.
2. The preparation process according to claim 1, characterized in that : In step 1, the concentration of the zirconium nitrate solution is 1-5wt%.
3. The preparation process according to claim 1, characterized in that In step 2, a mixed gas of a carbon source gas and an inert gas in a volume ratio of 1:2-3 is introduced, the temperature is raised to 900-1000° C., and maintained for 2-4 hours.
4. The preparation process according to claim 1, characterized in that : In the step 3, graphite emulsion, polycarbosilane with a molecular weight of 1000-2000, and silicon powder with a size of 100-150 nm are dispersed in tetrachloroethylene to obtain a slurry, wherein the mass ratio of graphite emulsion, polycarbosilane, silicon powder and tetrachloroethylene is 100:25-50:20-30:150-200, and then vinyl triethoxysilane is added, wherein the mass ratio of vinyl triethoxysilane to the slurry is 2-5:100; the slurry is coated on the surface of the product in step 2, dried and placed in a high-temperature furnace, and heated to 1100-1300° C. in a closed or inert atmosphere, maintained for 0.5-2 h, and then heated to 1800-2000° C. for graphitization, maintained for 0.5-1 h.
5. The preparation process according to claim 1, characterized in that : In the step 4, the silicon carbide nanowires and aminopropyltriethoxysilane are mixed in a mass ratio of 10:1-2, then added to toluene, heated for 4-6 hours for activation, and then dried; the dried silicon carbide nanowires are dispersed in an aqueous solution containing a carbon source precursor with a concentration of 15-20wt%, stirred evenly, filtered, dried, and then placed in a high-temperature furnace, heated to 600-700°C under inert gas protection for high-temperature carbonization to obtain modified silicon carbide nanowires.
6. The preparation process according to claim 1, characterized in that : In the step 5, the modified silicon carbide nanowires, polycarbosilane with a molecular weight of 1000-2000, and silicon powder with a particle size of 100-150nm are dispersed in tetrachloroethylene to obtain a slurry, wherein the mass ratio of the modified silicon carbide nanowires, polycarbosilane, silicon powder and tetrachloroethylene is 15-20:25-50:20-30:150-200, and then vinyl triethoxysilane is added, wherein the mass ratio of vinyl triethoxysilane to the slurry is 2-5:100; the slurry is coated on the surface of the product in step 3, placed in a high-temperature furnace, and heated at 1600-1800°C in a closed or inert atmosphere for 1-4h.
7. The preparation process according to claim 1, characterized in that : In the step 6, phenolic resin, fumed silica powder, and ethylene glycol are mixed in a mass ratio of 50-60:50-60:140-160 to obtain a slurry; the slurry is coated on the surface of the product in step 5, placed in a high-temperature furnace, and a mixed gas of monosilane and hydrogen in a volume ratio of 1:2-4 is introduced, the temperature is raised to 850-950°C, maintained for 10-16h, and cooled to obtain a carbon fiber thermal insulation material.
8. A carbon fiber thermal insulation material, characterized in that : The material is obtained by the preparation process described in any one of claims 1-7.
Citation Information
Patent Citations
Preparation method of silicon carbide coating on surface of hard carbon fiber felt
CN103993474A
Preparation method of high-strength and high-toughness silicon carbide nanowire reinforced silicon carbide ceramic composite material
CN111995418A
SiC composite coating for porous thermal insulation carbon material and preparation method thereof
CN112174684A
Preparation method of high-temperature antioxidant carbon fiber toughened zirconia ceramic material and high-temperature antioxidant carbon fiber toughened zirconia ceramic material
CN113845367A
Hard carbon fiber felt composite coating and preparation method thereof
CN115387131A